2022
DOI: 10.1155/2022/7519838
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Gene Signatures of m6ARNA Methylation Regulators in Lung Adenocarcinoma and Development of a Risk Scoring System

Abstract: The recent application of targeted immunotherapy has greatly improved the clinical outcomes of patients with lung adenocarcinoma (LUAD), but drug resistance continues to emerge, and to evaluate and to improve patient prognosis are arduous. The diagnostic and prognostic value of N6-methyladenosine (M6A) in LUAD has attracted increasing attention. We systematically studied correlations among important M6A methylation regulators, tumor mutational burden (TMB), and immune infiltration in clinical and sequencing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The latest data showed that global new lung cancer deaths in 2020 was close to 1.8 million 1 . Lung adenocarcinoma (LUAD), which is the predominate type of lung cancer 2 , 3 , has witnessed an increase in incidence in the last 15 years and become the most infiltrative form of lung cancer 4 , 5 . For LUAD patients, the treatment results are far from satisfactory due to the delay in diagnosis and limitations of traditional therapies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The latest data showed that global new lung cancer deaths in 2020 was close to 1.8 million 1 . Lung adenocarcinoma (LUAD), which is the predominate type of lung cancer 2 , 3 , has witnessed an increase in incidence in the last 15 years and become the most infiltrative form of lung cancer 4 , 5 . For LUAD patients, the treatment results are far from satisfactory due to the delay in diagnosis and limitations of traditional therapies 6 .…”
Section: Introductionmentioning
confidence: 99%